PENGARUH FAKTOR-FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM PADA PERUSAHAAN ASURANSI DI BEI 2009-2012 - Lambey, Robert (ACCOUNTABILITY, 2014)
The purpose of this study to know the influence of fundamental factors that ROA, DER, TATO, and CR on stock price. In this case the researchers used data in the form of financial statements food and beverage companies listed in Indonesia Stock Exchange (IDX). Researchers used a population of 10 companies listed on the Stock Exchange period 2009-2012. The data used financial statements are the financial statements that have been published in the Indonesian Capital Market Directory (ICMD) in 2013 and in www.idx.co.id. The analysis tool used is multiple regression analysis, t test, F test and the coefficient of determination was tested with the classical assumption. Based on the analysis of data it can be concluded that the variable DER and CR have a significant effect on stock price.